The expression of CTLA-4 in hepatic alveolar echinococcosis patients and blocking CTLA-4 to reverse T cell exhaustion in Echinococcus multilocularis-infected mice - Yang, Yuxuan; Wuren, Tana; Wu, Binjie; Cheng, Shilei; Fan, Haining (Frontiers in Immunology, 2024)
Alveolar echinococcosis (AE) is a zoonotic parasitic disease caused by the infection of Echinococcus multilocularis (E. multilocularis) larvae. Cytotoxic T-lymphocyte antigen 4 (CTLA-4) produces inhibitory signals and induces T cell exhaustion, thereby inhibiting the parasiticidal efficacy of the liver immune system. Therefore, the purpose of this manuscript is to explore how T-cell exhaustion contributes to AE, and whether blocking CTLA-4 could reverse T cell exhaustion. Here, we discovered that the expression of CTLA-4 was increased in the infiltrating margin around the lesion of the liver from AE patients by using western blot and immunohistochemistry assay. Multiple fluorescence immunohistochemistry identified that CTLA-4 and CD4/CD8 molecules were colocalized. For in vitro, it was found that sustained stimulation of E. multilocularis antigen could induce T cell exhaustion; blocking CTLA-4 reversed T cell exhaustion. For in vivo, the expression of CTLA-4 was increased in the liver of E. multilocularis infected mice, and the CTLA-4 and CD4/CD8 molecules were co-localized. Flow cytometry analysis demonstrated that the percentage of both CD4 + T cells and CD8 + T cells in the liver and peripheral blood were significantly increased and induced T exhaustion. When the mice were treated with anti-CTLA-4 antibodies, the number and weight of the lesions decreased significantly. Meanwhile, flow cytometry results suggested that blocking CTLA-4 could effectively reverse the T cell exhaustion and reactivate immune function.Our work reveals that blocking CTLA-4 could effectively reverse the T cell exhaustion caused by E. multilocularis, and could be used as a novel target for the treatment of AE.